2012
DOI: 10.1002/ar.22586
|View full text |Cite
|
Sign up to set email alerts
|

The use of Neurotrophin Therapy in the Inner Ear to Augment Cochlear Implantation Outcomes

Abstract: This review will cover the roles of neurotrophins in inner ear development, neuronal maintenance, neuronal process regeneration, and clinical applications including possible augmentation of cochlear implant function. Severe to profound deafness is most often secondary to a loss of or injury to cochlear mechanosensory cells, and there is often an associated loss of the peripheral auditory neural structures, specifically the spiral ganglion neurons and peripheral auditory fibers. Cochlear implantation is current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 99 publications
(150 reference statements)
0
41
0
1
Order By: Relevance
“…The electrical stimulation provided by cochlear implants is expected to support the survival of SGNs (Hegarty et al, 1997; Miller et al, 2003), but also limit SGN neurite growth (Roehm et al, 2008). In addition to neurotrophin therapy (Budenz et al, 2012), antagonizing CaBP1 signaling could offer a promising approach to overcoming current obstacles in cochlear implant therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The electrical stimulation provided by cochlear implants is expected to support the survival of SGNs (Hegarty et al, 1997; Miller et al, 2003), but also limit SGN neurite growth (Roehm et al, 2008). In addition to neurotrophin therapy (Budenz et al, 2012), antagonizing CaBP1 signaling could offer a promising approach to overcoming current obstacles in cochlear implant therapies.…”
Section: Discussionmentioning
confidence: 99%
“…145 Beside this, there are two advantages of such anatomical structures: first, the peri-and endolymphatic fluids provide a means for the distribution of BDNF throughout the whole cochlea and, second, BDNF delivered to the inner ear will not reach the systemic circulation, therefore, reducing adverse reactions to the organism. 146 Many experimental models have been presented to cause hearing loss. Traditionally, the combination of aminoglycosides and diuretics is considered to be a classical one.…”
Section: Bdnf As a Therapeutic Option For Deafnessmentioning
confidence: 99%
“…Recent treatment strategies of bionic cochlear implant use these growth factors to aid survival of cochlear ganglion neurons in deafened ear and enhancing therapeutic outcomes [10]. Many experimental studies have shown that whenever there is loss of neurotrophic support from these factors, the ganglion neurons appear unhealthy with smaller soma [19] and pyknotic, misshapen nuclei [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Till now various studies have been conducted on developing animals to understand morphometrical maturation of cochlear ganglion with detailed study on experimentally deafened animals to provide an insight for cochlear implant studies [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%